Efektivitas Pelaksanaan Sistem Penjaminan Mutu Internal Pada Perguruan Tinggi Swasta (Studi Kasus Universitas Mandiri Bina Prestasi) - Sartana; Fauzi Haris Simbolon; Ratna Wati Simbolon; Maradu Sihombing; Marice Hotnauli Simbolon (LOFIAN: Jurnal Teknologi Informasi dan Komunikasi, 2025)
Based on Minister of Education and Culture Regulation No. 53 of 2023, universities as educational institutions have a big responsibility to provide quality educational services through the Internal Quality Assurance System (SPMI). It is hoped that the presence of SPMI can make a positive contribution to the quality of education in a tertiary institution. SPMI can be called the foundation of higher education which must be implemented by ensuring that every element in the environment moves according to higher education standards. The implementation of SPMI has indeed become a benchmark for determining the quality of a tertiary institution, but there are still many who have not implemented it according to the standards that have been set, resulting in the level of effectiveness of implementing SPMI in tertiary institutions being low. The private university Mandiri Bina Prestasi University (UMBP) has complete SPMI documents and refers to Minister of Education and Culture Regulation No. 53 of 2023 and measures the level of effectiveness of SPMI implementation through SPMI implementation effectiveness indicators by conducting Internal Quality Audits (AMI) and Monitoring and Evaluation (Monev) on the performance and quality of each work unit within the UMBP environment including all Study Programs. In this way, by filling out questionnaires and questionnaires which are distributed to all elements and work units, the level of effectiveness of the implementation of SPMI at UMBP Higher Education can be measured, making it easier for decision makers and policy makers to improve and even increase the standards that apply at UMBP so that Good University Government can be achieved.